Beyond that, the sea [large type] - Spence-Ash, Laura (Thorndike Press large print core series., 2023)
"As German bombs fall over London in 1940, Millie and Reginald Thompson send their eleven-year-old daughter, Beatrix, to America for the duration of the war. The Gregorys fold Bea seamlessly into their world. She becomes part of this lively family, learning their ways and adjusting to their affluent lifestyle. Before long, life with the Gregorys feels more natural to her than the quiet, spare life with her own parents back in England. The girl she had been begins to fade away, until she is called home to London when the war ends. As she returns to post-war London, the memory of her American family stays with her as she tries to move on and pursue a life of her own"--